Adaptive management: Promises and pitfalls - McLain, Rebecca J.; Lee, Robert G. (Environmental Management, 1996)
Proponents of the scientific adaptive management approach argue that it increases knowledge acquisition rates, enhances information flow among policy actors, and provides opportunities for creating shared understandings. However, evidence from efforts to implement the approach in New Brunswick, British Columbia, Canada, and the Columbia River Basin indicates that these promises have not been met. The data show that scientific adaptive management relies excessively on the use of linear systems models, discounts nonscientific forms of knowledge, and pays inadequate attention to policy processes that promote the development of shared understandings among diverse stakeholders. To be effective, new adaptive management efforts will need to incorporate knowledge from multiple sources, make use of multiple systems models, and support new forms of cooperation among stakeholders.

America’s Most Successful Export to Japan: Continuous Improvement Programs - Dean M., Schroeder; Robinson, Alan G. (MIT Sloan Management Review, 1991)
CONTINUOUS IMPROVEMENT Programs (CIPs) unleash employee experience and I creativity to improve both products and processes. They are often cited as the most important difference between the Japanese and Western management styles and as a major factor in Japan’s economic success.2Yet the CIP was conceived, developed, and brought to maturation in the United States. After World War II, the U.S. government helped to export it to Japan, where it was well received and promptly flourished. Despite the long history and well-documented benefits of such systems, few U.S. companies have invested effort in CIPs equivalent to that of their Japanese competitors. Japanese companies have put almost forty years into the development and refinement of CIPs, or kaizen programs as they are known in Japan, and have brought the art and science of managing them to new levels of sophistication. The aim of these programs is precisely to design and implement a system whose natural equilibrium is constant improvement and change. How can a company that does not have such a program compete with one that does? In this paper we give the historical background of CIPs, which we believe is essential for a useful understanding of these programs. We document their export across the Pacific immediately following World War II and illustrate their power as a competitive weapon when fully and properly deployed. We then identify and discuss requirements for successful implementation and suggest reasons why many U.S. firms find them difficult to start and maintain. We conclude by arguing that what is commonly perceived to be the “best practice” of CIP management is itself open to improvement. Throughout the article, we identify promising directions for companies to pursue so that all minds in the company, not just those of a few at the top, are actively solving problems, reducing costs, and eliminating waste.

Appraising Adaptive Management - Lee, Kai (Conservation Ecology, 1999)
Lee, K. N. 1999. Appraising adaptive management. Conservation Ecology 3(2): 3. https://doi.org/10.5751/ES-00131-030203

Beyond methodologies: Coalition-building for participatory technology development - Biggs, Stephen; Smith, Grant (World Development, 1998)
Participatory and other approaches to technology development have shared a recent preoccupation with specific methods and doubts about just how much can be expected of the methods themselves, as opposed to how they are applied, by whom, and in what circumstances. Detailed analysis of historical cases suggests that the development of both technologies and methodologies is highly dependent on local context. Such processes are characterized by conflicts over the direction of change and affected by the activities of a particular type of grouping, the development coalition. These coalitions are examined and implications are considered for training, education and Participatory technology development.
Keywords: agricultural research; methods; participatory development; research and development; rural development; science and technology

Bringing politics back in: Towards a model of the developmental state - Leftwich, Adrian (The Journal of Development Studies, 1995)
The few cases of rapid economic growth in the Third World in the last 30 years have occurred in democratic, quasi‐democratic and non‐democratic polities. They are thus clearly not a function of common regime type. I suggest that they are best explained by the special character of their states, understood ‘as developmental states’. This article outlines some common characteristics of these states. However the forms and features of these states are not simply a function of their administrative structures or principles of governance, but of their politics. The article thus also underlines the importance of political analysis in both development theory and policy, from where it has been extruded for too long.

Building a Learning Organization - Garvin, David A. (Harvard Business Review, 1993)
Beyond high philosophy and grand themes lie the gritty details of practice.

Changing the way we change - Pascale, R.; Millemann, M.; Gioja, L. (Harvard Business Review, 1997)
More and more companies struggle with growing competition by introducing improvements into every aspect of performance. But the treadmill keeps moving faster, the companies keep working harder, and results improve slowly or not at all. The problem here is not the improvement programs. The problem is that the whole burden of change typically rests on so few people. Companies achieve real agility only when every function and process–when every person–is able and eager to rise to every challenge. This type and degree of fundamental change, commonly called revitalization or transformation, is what many companies seek but rarely achieve because they have never before identified the factors that produce sustained transformational change. The authors identify three interventions that will restore companies to vital agility and then keep them in good health: incorporating employees fully into the principal business challenges facing the company, leading the organization in a different way in order to sharpen and maintain incorporation and constructive stress, and instilling mental disciplines that will make people behave differently and then help them sustain their new behavior. The authors discovered these basic sources of revitalization by tracking the change efforts of Sears, Roebuck & Company, Royal Dutch Shell, and the United States Army. The organizations used these interventions to alter the way their people experienced their own power and identity, as well as the way they dealt with conflict and learning. As at Sears, Shell, and the U.S. Army, any major shift in those four elements will create a landmark shift in any organization's operating state or culture.
Keywords: Commerce; Conflict (Psychology); Decision Making; Organizational; Economic Competition; Leadership; Military Personnel; Organizational Culture; Organizational Innovation; Personnel Management; Power; Psychology; United States

Editorial: Responsible well-being — a personal agenda for development - Chambers, Robert (World Development, 1997)
If development means good change, questions arise about what is good, and what sorts of change matter. Answers can be personally defined and redefined. The changing words, meanings and concepts of development discourse both reflect and influence what is done. The realities of the powerful tend to dominate. Drawing on experience with participatory approaches and methods which enable poor and marginalized people to express their realities, responsible well-being is proposed as a central concept for a development agenda. This links with capabilities and livelihoods, and is based on equity and sustainability as principles. The primacy of personal actions and non-actions in development points to the need for a pedagogy for the non-oppressed. This includes self-critical awareness, thinking through the effects of actions, and enabling those with power and wealth to experience being better off with less. Others are invited and encouraged to reflect, improve on this analysis, and write their own agenda.
Keywords: development vocabulary; ethics; methods; participation; poverty; well-being

Growth of human factors in application development - Cockburn, Alistair (Humans and Technology Technical Report, 1995)

Guidelines for Drawing Causal Loop Diagrams - Daniel H., Kim (The Systems Thinker, 1992)
The old adage “if the only tool you have is a hammer, everything begins to look like a nail” can also apply to language. If our language is linear and static, we will tend to view and interact with our world as if it were linear and static. Taking a complex, dynamic, and circular world and linearizing it into a set of snapshots may make things seem simpler, but we may totally misread the very reality we were seeking to understand. Making such inappropriate simplifications “is like putting on your brakes and then looking at your speedometer to see how fast you were going” says Bill Isaacs of the MIT Center for Organizational Learning. Articulating Reality Causal loop diagrams provide a language for articulating our understanding of the dynamic, interconnected nature of our world. We can think of them as sentences which are constructed by linking together key variables and indicating the causal relationships between them. By stringing together several loops, we can create a coherent story about a particular problem or issue.

Learning to Learn: Improving International Governance - Haas, Peter M.; Haas, Ernst B. (Global Governance, 1995)

Messy, Exciting, and Anxiety-Ridden: Adaptive Software Development - Highsmith, Jim (American Programmer, 1997)

NGO Accountability: A Conceptual Framework - Najam, Adil (Development Policy Review, 1996)

PRA five years later - where are we now? / DRP - Cinco años después, ¿dónde nos encontramos? - Chambers, Robert; Guijt, Irene (Forest, Trees and People Newsletter, 1995)
PRA five years later: where are we now?

Trapped in a Treadmill: Bureaucratic Constraints on Aid Programs - Hoben, Allen (Harvard International Review, 1992)
Publisher: Harvard International Review